2020
DOI: 10.1371/journal.pone.0227047
|View full text |Cite
|
Sign up to set email alerts
|

LTA1 and dmLT enterotoxin-based proteins activate antigen-presenting cells independent of PKA and despite distinct cell entry mechanisms

Abstract: Enterotoxin-based proteins are powerful manipulators of mucosal immunity. The A1 domain of heat-labile enterotoxin from E. coli, or LTA1, is a newer adjuvant from this family under investigation for intranasal vaccines. Although LTA1 has been examined in mouse vaccination studies, its ability to directly stimulate immune cells compared to related adjuvant proteins has not been well explored. Here, we perform the first rigorous examination of LTA1's effect on antigen presenting cells (APC) using a human monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
1
8
1
Order By: Relevance
“…Interaction of cholera toxin with GM1 on gut dendritic cells is required for its oral adjuvanticity 146 , although the precise mechanisms of action are not fully resolved. NF-κB activation was required for the adjuvanticity of mmCT, with cyclic AMP–protein kinase A (cAMP–PKA) signalling proposed to be required for NF-κB activation in mmCT-stimulated dendritic cells in vitro 186 , although PKA may be dispensable for dendritic cell activation by dmLT 187 . Both dmLT and mmCT required cAMP–PKA-dependent inflammasome activation to promote human T H 17-type responses 188 .…”
Section: Mucosal Adjuvant Approachesmentioning
confidence: 99%
“…Interaction of cholera toxin with GM1 on gut dendritic cells is required for its oral adjuvanticity 146 , although the precise mechanisms of action are not fully resolved. NF-κB activation was required for the adjuvanticity of mmCT, with cyclic AMP–protein kinase A (cAMP–PKA) signalling proposed to be required for NF-κB activation in mmCT-stimulated dendritic cells in vitro 186 , although PKA may be dispensable for dendritic cell activation by dmLT 187 . Both dmLT and mmCT required cAMP–PKA-dependent inflammasome activation to promote human T H 17-type responses 188 .…”
Section: Mucosal Adjuvant Approachesmentioning
confidence: 99%
“…Th17 responses are known to be especially important for protection against mucosal pathogens, including Shigella (13,14). Unfortunately, recent studies showed that dmLT, when delivered IN, can cause Bell's palsy (11,15,16), however, the development of Bell's palsy from dmLT is related to the ability of the B subunit to bind to the gangliosides of neuron cells. It is the LTA1 (heat-labile enterotoxin A1) portion of the A subunit that is responsible for generating the Th17 response (15,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, recent studies showed that dmLT, when delivered IN, can cause Bell's palsy (11,15,16), however, the development of Bell's palsy from dmLT is related to the ability of the B subunit to bind to the gangliosides of neuron cells. It is the LTA1 (heat-labile enterotoxin A1) portion of the A subunit that is responsible for generating the Th17 response (15,17,18). To simplify and lower the costs of producing a Shigella spp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dmLT enhanced antibody responses to conjugate antigens using a polysaccharide-protein conjugate against V. cholerae 47 . We have also developed a B-subunit free adjuvant called LTA1 based on the A1 domain 39 , 48 , 49 . LTA1 was specifically developed for safe intranasal (IN) use to overcome the risk of Bell’s palsy with AB 5 LT proteins 48 , 50 , 51 .…”
Section: Introductionmentioning
confidence: 99%
“…LTA1 was specifically developed for safe intranasal (IN) use to overcome the risk of Bell’s palsy with AB 5 LT proteins 48 , 50 , 51 . Like dmLT, LTA1 also activates antigen presenting cells 49 and stimulates immunity to parenteral injection of vaccine antigen 52 . However, the ability of dmLT, LTA1, or any bacterial-enterotoxin based adjuvant for vaccines targeting substances associated with use disorders has not been explored (though the cholera toxin binding B-subunit has been used as a carrier for cocaine vaccines 16 ).…”
Section: Introductionmentioning
confidence: 99%